Strategi Alternatif untuk Akselerasi Pertumbuhan Bank Syariah: Penggabungan, Pemisahan, Akuisisi, dan Konversi - Mohammad Nur Rianto Al Arif; Aini Masruroh; Dwi Nuraini Ihsan; Yuke Rahmawati (Al-Ulum, 2020)
The year 2023 is the deadline for sharia business units to decide on the business strategy to be carried out. This study aims to determine alternative strategies that can be carried out by sharia business units in accelerating business growth. The approach taken in this paper is a mixture of qualitative and quantitative approaches. A qualitative approach using SWOT analysis and interviews. While the quantitative approach using ARIMA. The ARIMA results show that no sharia business unit can achieve a 50% share of assets from its parent bank. This shows the spin-off strategy as mandated by the law needs to be evaluated. Alternative strategies that can be done is conversion, where there are already two banks that do this strategy. Also, another alternative strategy that can be taken is a merger between Islamic business units. Another alternative strategy is the acquisition of sharia business units by established sharia full-fledged banks.